The enablers of early career outcomes of information technology professionals - Setor, Tenace Kwaku (2018)
The sustainability of digital economies requires that IT prospects find employment, persist and succeed in IT careers. IT research have yet to examine the enablers of these salient early career outcomes. Rather, the earlier studies have largely focused attention on the enablers of career outcomes related to mid to late career IT professionals. The insights proffered by the earlier studies fail to adequately explain the enablers of initial IT employment, early IT career persistence and success in terms accrued wages. This dissertation therefore begins a research agenda that extends the narrative of the extant research and focuses extensively on early career IT professionals. In doing so, I conduct two studies. Essay 1 focuses on college IT graduates by examining how college- based career interventions influence initial IT employment and career persistence. Drawing largely on the human capital literature, I formulate a set of hypotheses that relates high and low direct experiences gained from college- based career interventions to (1) the likelihood of initial IT employment and (2) IT career persistence. Results indicate that cooperative education, internship and mentorship experiences increase the likelihood of initial IT employment success. Further, I find that internship and mentorship experiences are strongly related to career persistence. Essay 2 focuses on early IT career success by asking whether IT graduates have more successful careers, in terms of accrued wages, compared to non-IT graduates who pursue IT careers. I synthesize arguments flowing from the human capital and the job-skills matching literatures and build a theoretical model that compares the wages of IT and non-IT graduates in IT careers. I find that IT degrees command higher wages than non-IT degrees.